2022
DOI: 10.1200/op.21.00634
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Hematology-Oncology Fellowship Programs: A Quantitative and Qualitative Survey Assessment of Fellowship Program Directors

Abstract: PURPOSE: The COVID-19 pandemic led to unprecedented challenges in medical training, and we sought to assess the specific impact of COVID-19 on hematology-oncology (HO) fellowship programs. METHODS: We conducted a cross-sectional anonymous online survey of 103 HO program directors (PDs) in conjunction with the American Society of Hematology (ASH) and ASCO. We sought to assess the specific impact of COVID-19 on HO fellowship programs' clinical, educational, and research activities, evaluate perceptions regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Prior to the COVID‐19 pandemic, this percentage might have been higher at this timepoint in the academic year. Several trainees and medical educators have commented on the specific difficulties of the job search due to the pandemic similarly to our respondents, including the virtual interview format and hiring freezes 11–13 . Outside of the pandemic, fellows and program leadership perceive a variety of barriers to the job search.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Prior to the COVID‐19 pandemic, this percentage might have been higher at this timepoint in the academic year. Several trainees and medical educators have commented on the specific difficulties of the job search due to the pandemic similarly to our respondents, including the virtual interview format and hiring freezes 11–13 . Outside of the pandemic, fellows and program leadership perceive a variety of barriers to the job search.…”
Section: Discussionmentioning
confidence: 76%
“…[11][12][13] Outside of the pandemic, fellows and program leadership perceive a variety of barriers to the job search. Perceived career development resource needs to help with the job search…”
mentioning
confidence: 99%
“…For instance, in HO, several studies have shown increased self-reported symptoms of burnout, stress, and worry regarding loss of clinical opportunities, grant funding, and variable productivity related to the COVID-19 pandemic, which may have influenced our findings. 29,30 For the bivariate association analysis, we reported the primary analysis results, where we included missing values as the not reported category. Our sensitivity analyses suggested that several findings from the primary analyses were not stable.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in HO, several studies have shown increased self-reported symptoms of burnout, stress, and worry regarding loss of clinical opportunities, grant funding, and variable productivity related to the COVID-19 pandemic, which may have influenced our findings. 29,30…”
Section: Discussionmentioning
confidence: 99%
“…The cardio-oncology fellows can actively engage in multi-center research projects, including collaboration with mentors virtually. Nevertheless, it is worth mentioning that the continuation of the COVID-19 pandemic has impacted physical, academic, as well as mental wellbeing of current cardio-oncology trainees [ 56 ]. Education institutions will need to remain vigilant and attentive on the mental and physical wellbeing of trainees to prevent unnecessary burnout [ 57 •].…”
Section: Growth and Incorporation Of Wearable Devices And Remote Digi...mentioning
confidence: 99%